Influence of Pulmonary Vascular Reserve on Exercise‐Induced Pulmonary Hypertension in Patients with Systemic Sclerosis. Issue 3 (8th August 2014) - Suzuki, Kengo; Izumo, Masaki; Kamijima, Ryo; Mizukoshi, Kei; Takai, Manabu; Kida, Keisuke; Yoneyama, Kihei; Nobuoka, Sachihiko; Yamada, Hidehiro; Akashi, Yoshihiro J.
<x xml:space="preserve">Abstract</x> Background Exercise‐induced pulmonary hypertension (PH) is considered as an early preclinical functional phase of resting PH in systemic sclerosis (SSc). In this study, we investigated the prevalence of exercise‐induced PH in patients with SSc and evaluated the influence of pulmonary vascular reserve on exercise‐induced PH. Methods This prospective study included 568 SSc patients. The patients with interstitial lung disease and those with left ventricular dysfunction were excluded (n = 50); finally, 518 patients underwent simple exercise echocardiography using a Master's two‐step. Systolic pulmonary artery pressure (SPAP), the ratio of early diastolic transmitral flow velocity to early diastolic mitral annular velocity (E/e') and pulmonary vascular resistance (PVR) were measured before and after exercise. ΔPVR (the difference between rest and post) was used for the assessment of pulmonary vascular reserve. All patients were stratified into the no exercise‐induced PH (SPAP <50 mmHg) or exercise‐induced PH (SPAP ≥50 mmHg, n = 133) group. Results Of the study patients, 27% patients were identified as having exercise‐induced PH. ΔPVR was higher in the exercise‐induced PH than no exercise‐induced PH group (0.2 ± 0.3 vs. 0.4 ± 0.4WU, P < 0.0001). A weak correlation was found between postexercise SPAP and postexercise E/e' (r = 0.31, P < 0.0001), whereas a strong correlation was found between postexercise SPAP and postexercise PVR (r = 0.62, P < 0.0001). The analyzed data demonstrated that ΔPVR was independently associated with exercise‐induced PH (odds ratio, 3.435; 95% CI, 1.013–11.650, P = 0.033). Conclusions The present study demonstrated that exercise‐induced PH was common in patients with SSc. Exercise‐induced PH might be closely associated with the factors affecting reduced pulmonary vascular reserve in patients with SSc.